Sosiologi Islam: Suatu Pengenalan - Hj. Ab. Majid, Mohamad Kamil (Jurnal Usuluddin, 1996)
Sociology is generally known to be an advanced developed discipline in the west. Nevertheless, we cannot deny the fact that it begins in the Islamic world by prominent figures such as al-Farabi (d. 950 M) and Ibn Khaldun (1406 M). This article exposes the contribution of Muqaddimah Ibn Khaldun which is discusess of sociologies’ theories. The existence of these proves that Islamic sociology is 400 years in advance of the western sociology. Nowadays, Islamic sociology has became a study of comparative sociology in sociology.